COVID 19 Dawn from Wuhan: “The Number Game” - Chawla, Sumit; Singh, Harinder; Chawla, Bharti (Indian Journal of Community Health, 2020)
On 31st December 2019, China informed local WHO office of "cases of pneumonia of unknown etiology detected in Wuhan. As of 6th May 2020, there are nearly 3.6 million cases of corona virus infection and approximately 0.25 million deaths worldwide. The real-time data regarding the actual number of cases, as it originates from the epicenter is the key to the estimation of the case fatality rate, hospitalization rates, expected timeline of arrival of contagion, and other epidemiological data. The novel virus has no available literature pertaining to its epidemiological parameters, on which experts can base their estimates and hence the challenge in planning for epidemic management. Bolstering this challenge are the reports alleging under-reporting by Chinese authorities. Alleged toned down numbers could have led to erroneously low estimates contributing to inadequate public health response globally. We conducted a simulation on epidemiological model of COVID-19 to find out expected time off arrival of infections and mortality in different countries and compared this to actual data.